2019
DOI: 10.3171/2017.7.jns171302
|View full text |Cite
|
Sign up to set email alerts
|

Bedside optical coherence tomography for Terson’s syndrome screening in acute subarachnoid hemorrhage: a pilot study

Abstract: OBJECTIVE Approximately 10% of patients with subarachnoid hemorrhage (SAH) become permanently, legally blind. The average cost of lifetime support and unpaid taxes for each blind person amounts to approximately $900,000. This study evaluates the feasibility and potential role of bedside optical coherence tomography (OCT) in Terson's syndrome (TS) in patients with acute SAH (aSAH) and its potential role in blindness prevention. METHODS The authors conducted an open-label pilot study, in which 31 patients with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…The gold standard for the screening of TS is direct and indirect funduscopy by an ophthalmologist [11,15]. However, various studies have shown that TS can also be diagnosed using ocular ultrasound (OU) and cCT [12,[16][17][18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…The gold standard for the screening of TS is direct and indirect funduscopy by an ophthalmologist [11,15]. However, various studies have shown that TS can also be diagnosed using ocular ultrasound (OU) and cCT [12,[16][17][18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, 31 patients with subarachnoid hemorrhage received both OCT scans with the Optovue iVue SD-OCT and dilated fundus examination. 3 OCT identified Terson syndrome in 7 patients (22.6%), whereas fundoscopy identified Terson syndrome in only 3 patients. 3 It is important to note that the small intraocular hemorrhages that were missed by indirect fundoscopy may not be clinically relevant and would be unlikely to require surgical intervention.…”
Section: Optical Coherence Tomography (Oct)mentioning
confidence: 96%
“…3 OCT identified Terson syndrome in 7 patients (22.6%), whereas fundoscopy identified Terson syndrome in only 3 patients. 3 It is important to note that the small intraocular hemorrhages that were missed by indirect fundoscopy may not be clinically relevant and would be unlikely to require surgical intervention. Bedside OCT seems to be a promising tool for the diagnosis of Terson syndrome.…”
Section: Optical Coherence Tomography (Oct)mentioning
confidence: 96%
See 2 more Smart Citations